2021
DOI: 10.1111/lam.13520
|View full text |Cite
|
Sign up to set email alerts
|

Association of Chlamydia trachomatis , Neisseria gonorrhoeae , Mycoplasma genitalium and Ureaplasma species infection and organism load with cervicitis in north Indian population

Abstract: Cervicitis is predominantly caused by Neisseria gonorrhoeae and Chlamydia trachomatis, which accounts for almost half of all the cases of cervicitis. The role of newer organisms like Mycoplasma genitalium and Ureaplasma sp. and association of bacterial load with cervicitis are also not well established. So the study aimed to determine the relative frequency of these organisms and their load in association with cervicitis cases from north India. A case–control study involving 300 women was conducted using quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 62 publications
0
8
1
Order By: Relevance
“…Bacterial load was not associated with cervicitis, whereas old age and irregularity in menstrual cycles were found to be associated with cervicitis. MG was the only bacterial pathogen that was found to be associated with cervicitis according to age, presence of discharge, and dysuria [ 22 ]. In contrast to the study carried out by Roy et al [ 22 ], in our study CT was the most frequently (21.4%) detected bacterial pathogen in cases with cervicitis, followed by MG and NG (3.1% each).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial load was not associated with cervicitis, whereas old age and irregularity in menstrual cycles were found to be associated with cervicitis. MG was the only bacterial pathogen that was found to be associated with cervicitis according to age, presence of discharge, and dysuria [ 22 ]. In contrast to the study carried out by Roy et al [ 22 ], in our study CT was the most frequently (21.4%) detected bacterial pathogen in cases with cervicitis, followed by MG and NG (3.1% each).…”
Section: Discussionmentioning
confidence: 99%
“…MG was the only bacterial pathogen that was found to be associated with cervicitis according to age, presence of discharge, and dysuria [ 22 ]. In contrast to the study carried out by Roy et al [ 22 ], in our study CT was the most frequently (21.4%) detected bacterial pathogen in cases with cervicitis, followed by MG and NG (3.1% each). Differences in the prevalence of CT, MG, and NG infections between the two studies may be attributed to geographical differences and demographical variations of the patients included.…”
Section: Discussionmentioning
confidence: 99%
“…The United States 2021 guidelines for the diagnosis and treatment of sexually transmitted diseases identified two major diagnostic signs that characterize cervicitis: (1) a purulent or mucopurulent endocervical exudate visible in the endocervical canal or on an endocervical swab specimen (commonly referred to as mucopurulent cervicitis) and (2) sustained endocervical bleeding easily induced by gentle passage of a cotton swab through the cervical os ( Workowski et al, 2021 ). C. trachomatis and N. gonorrhoeae are the two most frequent sexually transmitted pathogens that cause cervicitis, and studies have indicated M. genitalium infection as an important new causal pathogen ( Roy et al, 2021 ).…”
Section: Mycoplasma Genitalium and The Female Reproductive S...mentioning
confidence: 99%
“… 2 However, its potential for harm to the human body remains unclear. Some studies have shown that the rapid propagation of UU can cause pathological conditions such as genital tract infection, 3 genital tract blockage, 3 vaginitis, 4 cervicitis, 5 urethritis, 6 and prostatitis. 7 The latest research showed that UU is an important microorganism in the male reproductive tract and can affect the quality of sperm.…”
Section: Introductionmentioning
confidence: 99%